Sustitución parcial de harina de trigo (Triticum aestivum L) por harina de zapallo (Cucúrbita máxima) y su incidencia en las características biológicas, microbiológicas y sensoriales en la elaboración de extruidos de origen alimentario, en el Complejo Agroindustrial de la Universidad Estatal de Bolívar - Sánchez Malusin, Erika Anabel (2022)
The use of compound flours has been fundamental in the elaboration of products with greater nutritional properties. The raw materials used as a supplement are normally of animal and vegetable origin that are capable of providing nutrients. The pumpkin (Cucurbita Máxima D) has its nutritional contribution in fiber, cellulose, vitamin A, magnesium and its minimum contribution in calories contributes to the neutralization of gastric acids, enriches the blood, regulates the digestive system and reduces the risk of suffering from heart disease This is thanks to the antioxidant properties of β-carotene, by which it deactivates free radicals and traps oxygen. That is why this research proposes to evaluate the "Partial substitution of wheat flour (Triticum aestivum L) by pumpkin flour (Cucurbita maxima) and its incidence in the biological, microbiological and sensory characteristics in the elaboration of extrudates, with different speed of screw rotation at 120 rpm and 160 rpm at an extrudate processing temperature of 100 °C, 120 °C, 140 °C. 18 treatments with 2 repetitions were proposed, standing out as the best treatment T5 (80% wheat flour + 20% pumpkin flour) (at a screw speed of 160 rpm) (with an extrusion temperature of 120 ° C) was the best evaluated in color, smell, taste, texture and acceptability, according to the chosen hedonic scale, within the biological, microbiological characteristics, the final product presented 4.90% moisture, 0.03% ash, 8.72% of fiber, 6.92 of pH, 0.25% of titratable acidity 18.34% of fat, 8.05% of protein, 68, 68% of carbohydrates, our product shows higher percentages than the snacks that are offered in the market what makes the product obtained is innocuous, that is, suitable for human consumption.